ECONOMIC VALUE ADDED (EVA) dan MARKET VALUE ADDED (MVA) SEBAGAI ALAT UKUR KINERJA PERUSAHAAN - Fitriyah, Fitriyah (IQTISHODUNA, 2008)
Company performance is a measure that describes the financial condition of a company. The measurement of financial performance is based on the data gathered from financial reports made by the company. One of the popular measure for financial performance is financial ratios. However, financial ratios are only focused on accounting profit and do not include capital cost, so the resulting information cannot give adequate insight on the expected return from the investments made by the investors. In order to provide a solution for this challenge, a new concept has been proposed, that is economic value added (EVA) and market value added (MVA). EVA is a measure of added value generated by a company by reducing cost of capital that will indicated whether the rate of return is higher than the cost of capital expended for financing the investment. While MVA is a cumulative outcome of company performance which results from various investment which has been committed or is expected to be made. Hence, the success in terms of MVA is the success in maximizing the wealth of shareholders by allocating proper resources.EVA is calculated by subtracting after-tax net operating income from weighted average cost of capital (WACC). A positive EVA means that the company gains a greater return than the cost of capital, so that the investors will gain a return from their investment, and vice versa. MVA is calculated by subtracting equity market value with equity book value. Equity market value is calculated by multiplying the number of outstanding shares with share price, while equity book value is calculated by multiplying the number of outstanding shares with the nominal value per share. A positive MVA ( 1) means that that the management has been able to improve the wealth of the company and, by the same token, the investors' wealth, and vice versa.